Sphingosine-1-phosphate receptors control B-cell migration through signaling components associated with primary immunodeficiencies, chronic lymphocytic leukemia, and multiple sclerosis - Sic, Heiko; Kraus, Helene; Madl, Josef; Flittner, Karl-Andreas; von Münchow, Audrey Lilly; Pieper, Kathrin; Rizzi, Marta; Kienzler, Anne-Kathrin; Ayata, Korcan; Rauer, Sebastian; Kleuser, Burkhard; Salzer, Ulrich; et al. (Journal of allergy and clinical immunology, 2014)
Five different G protein–coupled sphingosine-1-phosphate (S1P) receptors (S1P1-S1P5) regulate a variety of physiologic and pathophysiologic processes, including lymphocyte circulation, multiple sclerosis (MS), and cancer. Although B-lymphocyte circulation plays an important role in these processes and is essential for normal immune responses, little is known about S1P receptors in human B cells. To explore their function and signaling, we studied B-cell lines and primary B cells from control subjects, patients with leukemia, patients with S1P receptor inhibitor–treated MS, and patients with primary immunodeficiencies. S1P receptor expression was analyzed by using multicolor immunofluorescence microscopy and quantitative PCR. Transwell assays were used to study cell migration. S1P receptor internalization was visualized by means of time-lapse imaging with fluorescent S1P receptor fusion proteins expressed by using lentiviral gene transfer. B-lymphocyte subsets were characterized by means of flow cytometry and immunofluorescence microscopy. Showing that different B-cell populations express different combinations of S1P receptors, we found that S1P1 promotes migration, whereas S1P4 modulates and S1P2 inhibits S1P1 signals. Expression of CD69 in activated B lymphocytes and B cells from patients with chronic lymphocytic leukemia inhibited S1P-induced migration. Studying B-cell lines, normal B lymphocytes, and B cells from patients with primary immunodeficiencies, we identified Bruton tyrosine kinase, β-arrestin 2, LPS-responsive beige-like anchor protein, dedicator of cytokinesis 8, and Wiskott-Aldrich syndrome protein as critical signaling components downstream of S1P1. Thus S1P receptor signaling regulates human B-cell circulation and might be a factor contributing to the pathology of MS, chronic lymphocytic leukemia, and primary immunodeficiencies.